Training on Developing Integrative Digital Teaching Materials for Teachers at Islamic Boarding Schools in Kartasura - Mokhamad Azis Aji Abdilah; Toto Suharto; Muhammad Zaenuri; Yasmin Roona; Zulva Wahyu Mumpuni Eka Putra; Annya Wening Salsabila (Transformatif: Jurnal Pengabdian Masyarakat, 2025)
Community service conducted by lecturers from the Arabic Language Education Study Program at UIN Raden Mas Said Surakarta involved training on developing integrative digital teaching materials for 43 teachers from six Islamic boarding schools (pesantren) in Kartasura. This activity employed a Participatory Action Research (PAR) approach to enhance teachers' competencies in designing digital teaching materials relevant to the characteristics of santri (students), particularly those who are also university students with dual schedules. The planning phase involved initial observations, in-depth interviews, problem mapping using the problem tree technique, and a pretest questionnaire, revealing that 93% of teachers faced difficulties in creating digital teaching materials, only 40% had limited prior experience, and 94% expressed the need for further mentoring. The training produced prototypes such as interactive slides, infographics, and short videos, fostering cross-pesantren collaboration. Post-training questionnaire analysis showed significant improvements (mean scores 3.68–4.12; p < 0.01), although infrastructure barriers persisted. These findings reinforce the effectiveness of participatory interventions in supporting digital transformation in Islamic education at the local level, with recommendations for ongoing mentoring and a shared repository.